A mixed strategy to fabricate two bifunctional ligand-based Ag-complexes with high proton conductivity. (20th September 2022) - Wang, Shuyu; Zhao, Lijia; Fang, Fang; Wang, Lei; Zhang, Zhen; Zhang, Suoshu; Du, Lin; Zhao, Qi-Hua
Abstract : High proton conductivity materials BAg-1 and BAg-2 were obtained using a mixed strategy with the same main bifunctional ligand. Abstract : In this work, a bifunctional ligand 2, 2′-disulfonic acid benzidine (H2 L) was selected, and we adopted a mixed ligand strategy, in which the ligand reacted with 2, 2′-bipyridine and 1, 10- o -phenanthroline, where two new silver-based coordination polymer materials [Ag2 (2, 2′-bipy)2 L]·H2 O (BAg-1 ) and [Ag2 (phen)2 L] (BAg-2 ) were obtained. BAg-1 was zero-dimensional, which could interconnect with one-dimensional hydrogen bonds to form a three-dimensional stacking structure, while BAg-2 was a one-dimensional chain structure, and the one-dimensional chains formed a two-dimensional planar structure through hydrogen bonding between the sulfonic acid group and the amino group. Their proton conductivity reached a high level among the coordination polymers at 98% relative humidity (RH) and 90 °C, where their proton conductivity values were 0.455 × 10 −4 S cm −1 (BAg-1 ) and 1.09 × 10 −4 S cm −1 (BAg-2 ), respectively. Combining their respective single crystal data with the results of Hirshfeld surface analysis, water adsorption experiments, and activation energy calculations, we determined their proton conduction pathways and mechanisms. The results showed that the abundant hydrogen bond chains and hydrogen bond networks co-constructed using sulfonic acid groups, amino groups and crystal water molecules in the framework and numerous uncoordinated sulfonic acid groups as proton carriers in the material were the reasons for efficient proton transfer.